Effect of Well Orientation on Oil Recovery from Waterflooding in Shallow Green Reservoirs: A Case Study from Central Africa - Jackson Waburoko; Congjiao Xie; Kegang Ling (Energies, 2021)
Recovery efficiency is a key factor in decision-making in oil and gas projects. Although structural setup and well type considerably influence waterflood recovery, few studies have explored the performance of highly deviated wells during the waterflooding of complex shallow reservoirs. Here, we applied numerical simulations to investigate the performance of vertical, horizontal, multilateral, and highly deviated wells during waterflooding of complex shallow reservoirs using the J1 Oilfield as a case study. Recovery efficiencies of 31%, 33%, 31%, and 26% could be achieved for vertical, horizontal, multilateral, and highly deviated wells, respectively. The gas production rate was 39% higher in the vertical wells than in the other types. Highly deviated wells yielded the highest water-cut (80%) over a short period. Highly deviated wells delivered the least production, and, despite branching laterals, multilateral wells were also not the most productive. Our results provide insights into the performance of different well types during the waterflooding of green heterogeneous non-communicating reservoirs and present an example of the successful practical application of waterflooding as an initial recovery mechanism when oil is near the bubble point. This study indicated that multilateral wells are not a panacea in reservoir development. Highly deviated wells are the ideal choice for the shallow, heterogeneous non-communicating reservoirs when economic and environmental impact are considered in decision-making. Well design should be a case-by-case study considering reservoir characteristics, economics, and environment impact.